Marianne or Germania? Nationalizing women in Alsace, 1870 - 1946 - Vlossak, Elizabeth (Oxford Univ. Press, 2010)
Schooling the step-daughters of Germania : education and the press, 1871-1914 -- An Alsatian women's movement : nation, region, confession, and the limits of German feminism, 1874-1914 -- Alsatian women and the Great War, 1914-18 -- Rebuilding French Alsace : language, myth, and the Republican ideal, 1914-24 -- "Malaise Alsacien" : malaise feminin : Alsatian women's identity in question, 1918-39 -- From Nazi re-annexation to full citizenship : the final stage of nationalization, 1940-6